2013
DOI: 10.7566/jpsj.82.094702
|View full text |Cite
|
Sign up to set email alerts
|

Flow and Tilt-Induced Orientation of the Moving Vortex Lattice in Amorphous NbGe Superconducting Thin Films

Abstract: The orientation and deformation of moving vortex lattices in the flux-flow state have been investigated in amorphous superconducting NbGe thin films. Employing a mode-locking technique, we detect how moving lattices deform and their orientation changes as a magnetic field is tilted from normal to the film surface. For high tilt angles the lattice orientation is aligned parallely with the tilt direction. Meanwhile for low tilt angles the lattice orientation depends on the vortex velocity and a velocity-induced … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
2
3
0
Order By: Relevance
“…Our results based mainly on the v ac dependence of ML at θ =36 • are qualitatively consistent with the results reported in Ref. 29. To elucidate the influence of both v dc and v ac on the lattice orientation, further ML measurements for different f ext are in progress.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Our results based mainly on the v ac dependence of ML at θ =36 • are qualitatively consistent with the results reported in Ref. 29. To elucidate the influence of both v dc and v ac on the lattice orientation, further ML measurements for different f ext are in progress.…”
Section: Resultssupporting
confidence: 91%
“…By contrast, when the moving lattice is expanded perpendicularly to the flow direction, only the perpendicular orientation is observed up to the largest v e studied. The results indicate that the distortion in the vortex lattice largely affects the orientation of the driven lattices and are qualitatively consistent with the recent ML measurements with small v ac , where v dc -and tilt-induced reorientation was studied [29]. We also point out that µSR measurements using slow muons that can be implanted into a thin film are highly desired to explore the dynamic ordering and rearrangement of the fast moving vortex lattices driven only by dc current.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the transient process, the vortex-vortex (v-v) interaction is considered to be isotropic. On the other hand, under the tilted (θ = 36 • ) field, an ordered vortex configuration both for the undriven case and fast-driven steady-state case shows an expanded hexagonal lattice by a factor of 1/cosθ(≈ 1.24) along the tilt direction [15][16][17][18]. Thus, the v-v interaction along the perpendicular direction (p-direction) to the tilt direction is stronger than that along the tilt direction (t-direction).…”
Section: Resultsmentioning
confidence: 99%
“…However, when the magnetic field is tilted from normal to the sample plane, the vortex configuration and the resultant inter-vortex interaction become anisotropic. Recent studies have revealed that when the magnetic field is tilted at θ from normal to the sample plane, hexagonal vortex lattice is expanded by a factor of 1/cosθ along the tilt direction [15][16][17][18]. More recently, we have found that the relation between the dynamic melting field and the velocity of the driven anisotropic lattice changes depending on the direction of the dc drive [18], indicating that not only the static vortices but also the moving vortices feel the anisotropic interaction.…”
mentioning
confidence: 79%